Literature reviews, citation management and other library support for your research - Stieglitz, Tara; Nelson, Jody (My University, 2015)
Learn how to conduct a systematic literature review taking advantage of the different strengths of different databases. Use techniques such as citation chaining and searching withe subject headings to expand your search. The presentation will also highlight the features of different citation management programs with a focus on Zotero.
Presented on April 27, 2015 to nursing faculty at MacEwan University in Edmonton, Alberta.
Keywords: nursing scholarship; literature reviews; reference management; library